2016
DOI: 10.1007/s10068-016-0274-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of malic acid or/and grapefruit seed extract for the inactivation of common food pathogens on fresh-cut lettuce

Abstract: This study investigated the antimicrobial activity of malic acid (MA), grapefruit seed extract (GSE), and combined (MA+GSE) treatment against O157:H7, Typhimurium, and on fresh-cut lettuce. The antimicrobial effects of 1% MA and 0.5% GSE alone and in combination (1% MA+0.5% GSE) were tested on artificially inoculated lettuce during storage at 5°C for 14 days. The maximum reductions of O157:H7, S. Typhimurium, and were 4.96, 4.80, and 3.95 log CFU/g observed with MA+GSE during storage for 14 days, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Moreover, this treatment enhanced the chlorogenic acid in Malus pumila by up to 56 % compared to the control. Kim et al [57] studied the antimicrobial effect of malic acid (1 %), Vitis vinifera seed extract (0.5 %), and combined treatment (1 % malic acid+0.5 % Vitis vinifera seed extract) on lettuce stored at 5 ℃ for 14 days. They have reported that the highest antimicrobial effect (log10 CFU/g) against…”
Section: Applications Of By-products In Food Preservationmentioning
confidence: 99%
“…Moreover, this treatment enhanced the chlorogenic acid in Malus pumila by up to 56 % compared to the control. Kim et al [57] studied the antimicrobial effect of malic acid (1 %), Vitis vinifera seed extract (0.5 %), and combined treatment (1 % malic acid+0.5 % Vitis vinifera seed extract) on lettuce stored at 5 ℃ for 14 days. They have reported that the highest antimicrobial effect (log10 CFU/g) against…”
Section: Applications Of By-products In Food Preservationmentioning
confidence: 99%
“…In regards to grapefruit seed extract, Kim et al [ 42 ] conducted a study on its antimicrobial efficacy against E. coli O157:H7, S. typhimurium , and L. monocytogenes inoculated in fresh-cut lettuce, alone and in combination with malic acid. Fresh-cut lettuce was stored at 5 °C, and its microbial quality was monitored over a period of 14 days.…”
Section: By-products Applied To Fresh-cut Producementioning
confidence: 99%
“…Hence, it could be concluded that the treatment with cashewnut and coconut extracts are more effective to reduce the foodborne pathogens on fresh-cut papaya. Studies in the past have also reported the antibacterial effectiveness of natural substances against foodborne pathogens (Park et al 2011;Kim et al 2016).…”
Section: Food Preservation Studiesmentioning
confidence: 99%